2022
DOI: 10.1002/eat.23683
|View full text |Cite
|
Sign up to set email alerts
|

Prone to food in bad mood—Emotion‐potentiated food‐cue reactivity in patients with binge‐eating disorder

Abstract: Objective: Theories on emotional eating are central to our understanding of etiology, maintenance, and treatment of binge eating. Yet, findings on eating changes under induced negative emotions in binge-eating disorder (BED) are equivocal. Thus, we studied whether food-cue reactivity is potentiated under negative emotions in BED, which would point toward a causal role of emotional eating in this disorder.Methods: Patients with BED (n = 24) and a control group without eating disorders (CG; n = 69) completed a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Another recent review found that interventions aiming at reducing EE also led to a significant weight reduction in individuals with overweight or [ 52 ]. Previous research also demonstrated the clinical importance of EE in eating disorders, such as AN, bulimia nervosa and binge-eating disorder [ 6 , 7 , 31 ]. Consistently across different countries, binge eating is more common in individuals with higher EE [ 53 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another recent review found that interventions aiming at reducing EE also led to a significant weight reduction in individuals with overweight or [ 52 ]. Previous research also demonstrated the clinical importance of EE in eating disorders, such as AN, bulimia nervosa and binge-eating disorder [ 6 , 7 , 31 ]. Consistently across different countries, binge eating is more common in individuals with higher EE [ 53 ].…”
Section: Discussionmentioning
confidence: 98%
“…Then, the EE task was conducted. After the EE task (described in detail below; data previously reported in [ 6 , 28 , 31 ]), a decision-making task (data previously reported in [ 32 34 ]) and a taste test followed.…”
Section: Methodsmentioning
confidence: 99%
“…We chose intensity of food cravings (FC; defined as the desire or urge to consume a specific palatable type of food; Cepeda-Benito et al, 2000;Gendall et al, 1997) as outcome variable. (Causal) links between higher FC and negative affective states have been shown in laboratory studies (Arend et al, 2022;Schnepper et al, 2021) andFC diaries (Waters et al, 2001) in BN and BED.…”
Section: Aimsmentioning
confidence: 90%
“…Similarly, transient factors and states, such as the time of day, surrounding environment, sleep duration, level of psychological stress, emotional state, physical activity, and levels of appetite-regulating hormones (e.g., circulating levels of leptin, ghrelin, PYY, endogenous GLP-1, and GLP-1RAs), have been associated with varying levels of food cue reactivity [46,[51][52][53][54][55][56][57][58][59][60][61].…”
Section: The Cue-influencer-reactivity-outcome (Ciro) Model Of Food C...mentioning
confidence: 99%